2018
DOI: 10.1371/journal.pone.0184873
|View full text |Cite|
|
Sign up to set email alerts
|

Serum selenium levels and the risk of progression of laryngeal cancer

Abstract: BackgroundObservational studies have reported an inverse relationship between selenium status (blood or toenail) and the risk of laryngeal cancer; however, the impact of low serum selenium level on survival has not been evaluated.MethodsWe conducted a prospective study of 296 patients diagnosed with laryngeal cancer in Szczecin, Poland. Serum selenium was measured at diagnosis and prior to treatment. Patients were followed from the date of diagnosis to death at five years. Vital status was obtained by linkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
1
20
0
2
Order By: Relevance
“…Indeed, several studies reported an inverse relationship between selenium levels and cancer risk. Recently, Lubiński et al (2018) highlighted that in laryngeal cancer patients, the selenium level at the time of diagnosis was associated with the outcome [ 9 ]; similarly selenium supplementation in women undergoing treatment for breast cancer can favorably influence the patients’ outcomes [ 10 ]. Recently, two reviews highlighted the association between single selenoproteins and either colorectal or prostate cancer initiation and progression, as well as patient outcome, suggesting that these proteins could represent potential biomarkers or therapeutic targets [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies reported an inverse relationship between selenium levels and cancer risk. Recently, Lubiński et al (2018) highlighted that in laryngeal cancer patients, the selenium level at the time of diagnosis was associated with the outcome [ 9 ]; similarly selenium supplementation in women undergoing treatment for breast cancer can favorably influence the patients’ outcomes [ 10 ]. Recently, two reviews highlighted the association between single selenoproteins and either colorectal or prostate cancer initiation and progression, as well as patient outcome, suggesting that these proteins could represent potential biomarkers or therapeutic targets [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serum selenium, iron, zinc, and copper levels were quantified by inductively coupled mass spectroscopy (ICP-MS NexION 350D, PerkinElmer) using methane to reduce polyatomic interferences, following Lubinski et al [20,21]. Calibration standards were prepared by diluting 10 mg/L Multi-Element Calibration Standard 3 (PerkinElmer Pure Plus, PerkinElmer Life and Analytical Sciences, USA) with a blank reagent consisting of a 0.65% solution of nitric acid (Merck, Germany) and 0.002% Tryton X-100 (PerkinElmer, USA).…”
Section: Element Assaymentioning
confidence: 99%
“…Another bioelement, selenium (Se), also affects redox status on account of its antioxidative properties [8,23]. Notably, it can be used as a cancer marker [20,21]. According to the statistics, transplant recipients are highrisk cancer patients [4,5,37].…”
Section: Introductionmentioning
confidence: 99%
“…In einer weiteren Beobachtungsstudie aus Polen zeigten sich vergleichbare Daten bei Patienten mit Larynxkarzinomen [93].…”
Section: Hno-tumorenunclassified